SOCIAL NETWORK ANALYSIS: A COMPETITION IN INDONESIA’S FASTEST GROWING FINTECH - Chandra Arifianto; Veritia Veritia (Jurnal Manajemen dan Kewirausahaan, 2022)
This study aimed to analyze how effective the use of social media was to maximize recognition and sales. On social media, users had tried to reveal information they already knew about financial technology startup businesses. User Generated Content (UGC) information, which was a track record left by users on social media, can be used as a mapping for users who communicate on social media. This study itself had used this phenomenon to measure the performance of companies (through brands) that were popular on social media, namely Gopay and DANA, in an effort to measure a person's awareness and interest. The method used was Social Network Analysis (SNA). This qualitative research aimed to describe the results of a phenomenon that were occurs. The results of this study indicated that DANA had advantages in the community and it was easy for users to communicate because there were few accounts that must be passed in conveying information. Meanwhile, Gopay had the advantage of having a large number of users and being have many relationships between users.